Experimental Study on Flexural Behaviour of Lightweight Multi-Ribbed Composite Slabs - Wei Huang; Xiang Ma; Bin Luo; Zeliang Li; Yujiao Sun (Advances in Civil Engineering)
To develop new slabs with light weight and high rigidity as well as meet the requirements of use and facilitate construction, a large-span multi-ribbed composite slab (R-CS) with filled lightweight blocks is proposed based on systematic research. Static tests of the bending behaviour of the four pieces of the R-CS specimens and one ordinary concrete cast-in-place slab were carried out. The fracture distribution, bearing capacity, deflection, and load-strain curves of the tensile steel bars were analysed. The difference in the bending behaviour between the R-CS specimens and the cast-in-place slab and the influence of different structural forms on the bending behaviour of the R-CS samples were studied. By calculating the bearing capacity of the fully composite state, their composite performance was evaluated. The research shows that the bending failure process of the R-CS specimens is similar to that of the cast-in-place slab and the crack and deflection development as well as ductility are relatively good. The measured bearing capacity of the specimen can reach more than 70% of the theoretical calculation strength under the fully composite state. The composite performance is satisfactory.